Potensi dan Strategi Pengembangan Wisata Goa Pancur dalam Meningkatkan Ekonomi Warga Lokal - Suparwi, Suparwi; Rakhmawati, Ita (BISNIS, 2021)
The main purpose of this study was to identify and identify and analyze the potential and strategies for developing Goa Pancur tourism in Jimbaran Kayen Pati Village in improving the local tourism economy. First, what is the potential of Goa Pancur tourism so that it has differentiation from other tours. Second, formulating the right strategy to increase the number of tourists and third, what is the right development strategy in increasing the local tourism economy. The data analysis method used descriptive qualitative analysis. From the results of the analysis, it was found that the tourism potential of Pancur Cave is very large but its development has not been maximized, especially the Pancur Cave itself and the existence of a swamp in front of the cave which is very different from other tours. The development strategy in increasing tourists uses a porter approach in which tourism differentiation must be maximized, tourism cost leadership to be maintained and finally segmentation efforts need to be carried out in its development. The future development strategy to improve the local economy is the stability strategy,